Back to the Future: Aesthetics Today - Shusterman, Richard (The Nordic Journal of Aesthetics, 2012)
This paper originated as the keynote address at the conference “Aesthetics Today” organized by the Finnish Society of Aesthetics to mark its 40th anniversary and was delivered at the University of Helsinki on March 1, 2012. Written for that particular occasion the sense of an oral presentation has been maintained. Shusterman’s point of departure is the thesis that contemporary aesthetics can be characterized by a number of leading themes that mark a return to older aesthetic perspectives, after these perspectives have been neglected in modern philosophical discussions. The paper briefly outlines and explores three of these themes whose increasing importance in current aesthetics can appeal to historical antecedents, namely: a focus on perception, the expansion of the aesthetic field beyond the philosophy of fine art, and the close connection of the aesthetic and the practical. After that, Shusterman formulates a fourth theme in aesthetics today which incorporates the first three and whose value for contemporary aesthetics he seeks to highlight, namely: the somatic, as exemplified by somaesthetics.